Bird Functional Diversity in Agroecosystems and Secondary Forests of the Tropical Andes - Vanessa Velásquez-Trujillo; Juan F. Betancurt-Grisales; Angela M. Vargas-Daza; Carlos E. Lara; Fredy A. Rivera-Páez; Francisco E. Fontúrbel; Gabriel J. Castaño-Villa (Diversity, 2021)
Agricultural systems have increased in extension and intensity worldwide, altering vertebrate functional diversity, ecosystem functioning, and ecosystemic services. However, the effects of open monoculture crops on bird functional diversity remain little explored, particularly in highly biodiverse regions such as the tropical Andes. We aim to assess the functional diversity differences of bird guilds between monoculture crops (coffee, cocoa, and citrus) and secondary forests. We use four functional diversity indices (Rao Q, Functional Richness, Functional Evenness, and Functional Divergence) related to relevant morphological, life history, and behavioral traits. We find significant differences in functional diversity between agroecosystem and forest habitats. Particularly, bird functional diversity is quite homogeneous among crop types. Functional traits related to locomotion (body weight, wing-chord length, and tail length), nest type (closed), and foraging strata (canopy and understory) are dominant at the agroecosystems. The bird assemblages found at the agroecosystems are more homogeneous in terms of functional diversity than those found at the secondary forests, as a result of crop structure and management. We recommend promoting more diverse agroecosystems to enhance bird functional diversity and reduce their effects on biodiversity.